Use of arbuscular mycorrhizal fungi and phosphorus for increase in the concentration of compounds with antioxidant activity in Libidibia ferrea (Research, Society and Development, 2021)
The increase of the concentration of secondary compounds in medicinal plants can be influenced by the association with arbuscular mycorrhizal fungi (AMF). Pharmacological studies have shown that secondary compounds, found ing Libidibia ferrea (Mart. ex Tul.) L. P. Queiroz, confer phytotherapeutic potential to the species due to antidiabetic, antibiotic and anticancer activity. Therefore, the aim of this work was to verify if the presence of AMF associated or not with phosphate fertilization has an effect on the concentration of foliar phenolic compounds with antioxidant activity in L. ferrea seedlings. The seedlings were transferred to pots with 1.2 kg of soil with phosphate fertilization (P2O5) or not. In the roots was deposited soil-inoculum, containing 300 spores {100 spores of each AMF species: Claroideoglomus etunicatum, Gigaspora albida and Acaulospora longula Acaulospora longula. The plants were maintained in greenhouse for seven months. AMF favored an increase in shoot dry matter production, accumulation of flavonoids and greater total antioxidant activity, dispensing fertilization of the soil. The mycorrhizal inoculation associated with phosphate fertilization maximized the biosynthesis of total chlorophyll and soluble carbohydrates. AMF inoculation presents as a possible biotechnological alternative to increase antioxidant activity and foliar flavonoid production in L. ferrea seedlings, avoiding expenses with agricultural inputs, such as phosphate fertilization, making phytomass more attractive for the production of phytotherapics.